2006
DOI: 10.1103/physreva.73.040702
|View full text |Cite|
|
Sign up to set email alerts
|

Feshbach spectroscopy of aKRbatomic mixture

Abstract: We perform extensive magnetic Feshbach spectroscopy of an ultracold mixture of fermionic 40 K and bosonic 87 Rb atoms. The magnetic-field locations of 14 interspecies resonances is used to construct a quantum collision model able to predict accurate collisional parameters for all K-Rb isotopic pairs. In particular we determine the interspecies s-wave singlet and triplet scattering lengths for the 40 K-87 Rb mixture as (−111 ± 5)a0 and (−215 ± 10)a0 respectively. We also predict accurate scattering lengths and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(66 citation statements)
references
References 35 publications
2
62
2
Order By: Relevance
“…This upper limit coincides with the value deduced from the first 40 K- 87 Rb spectroscopy experiment at JILA and the corresponding resonance assignment. The identification of more Feshbach resonances and an upgraded collisional model performed at LENS as well as an improved magnetic field calibration has resulted in a scattering length of −215(10) a 0 [61], and the upper limit reported here is compatible with that value. Since the same argument is valid for any experiment, there is no contradiction between the observed stable particle number combinations and a F B = −215(10) a 0 .…”
Section: Excitationssupporting
confidence: 63%
See 2 more Smart Citations
“…This upper limit coincides with the value deduced from the first 40 K- 87 Rb spectroscopy experiment at JILA and the corresponding resonance assignment. The identification of more Feshbach resonances and an upgraded collisional model performed at LENS as well as an improved magnetic field calibration has resulted in a scattering length of −215(10) a 0 [61], and the upper limit reported here is compatible with that value. Since the same argument is valid for any experiment, there is no contradiction between the observed stable particle number combinations and a F B = −215(10) a 0 .…”
Section: Excitationssupporting
confidence: 63%
“…While the coherence properties of the pure bosonic system (loss of coherence with increasing lattice depth) can be explained in terms of the superfluid to Mott-insulator transition and the associated many-body wavefunctions in the superfluid and the Mottinsulating regime, the nature of the observed shift of the coherence properties towards lower optical lattice depth in the mixture is still a point of intense discussions in the community. Possible scenarios include thermodynamic effects like adiabatic heating when ramping up the optical lattice, disorder-induced localization scenarios or a shift of the quantum critical point of the bosonic superfluid to Mott-insulator transition due to attractive interactions with the fermionic atoms (a FB = −215(10) a 0 [61]). In parallel to this work, similar studies and results have been reported at ETH Zürich [109].…”
Section: Fermi-bose Mixtures In Optical Latticesmentioning
confidence: 99%
See 1 more Smart Citation
“…This amounts to producing a mixed MOT of the two species and then evaporatively cool 87 Rb allowing K to thermalize with it. With this technique it has been possible to reach quantum degeneracy of 40 K [9] and 41 K [10], but no attempts have been made to test this method on 39 K. For this mixture in fact, the inter-species cross section is again more than one order of magnitude smaller than the one of 87 Rb-40 K and 87 Rb-41 K [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the work presented in this paper is a critical step towards the production of a Bose-Einstein Condensate (BEC) of 39 K. Such a system is a promising candidate for the realization of a BEC with interaction tunable around zero, since a broad Feshbach resonance is predicted around 400 G [11,12].…”
Section: Introductionmentioning
confidence: 99%